Nuovi aspetti teorici e metodologici della supervisione nelle strutture pubbliche - Andrea Masini (Il sogno della farfalla, 2021)
Drawing from reflections on supervision reported by Massimo Fagioli in his written work, the author proposes some clinical experiences carried out in Mental health outpatient services with the aim of highlighting both limits and new practical possibilities of this well-known practice.